'I believed I could, so I did'—A theoretical approach on self-efficacy beliefs to positively influence men with a risk to sexually abuse children. (November 2015) - Tozdan, Safiye; Briken, Peer
Abstract: Today's competing positions regarding the flexibility of pedophilic sexual interest are of increasing relevance. Besides empirical research on this specific topic, theoretical work grounded on scientifically sound research is equally needed. From a theoretical perspective, this paper aims to deduce if self-efficacy to change sexual interest in children may influence men with a risk to sexually abuse children in a positive way. We focus on research literature on (1) self-efficacy and (2) sexual interest in children in order to (3) link both. By this, we provide a framework within which sexual interest in children may also be seen as flexible and changeable due to specific therapeutic interventions. By addressing the individuals' conviction of being able to alter their sexual interest in children, the required motivation for change might be enhanced and help the individuals in changing and developing. Finally, both research and clinical implications are given. Highlights: We theoretically link sexual interest in children with self-efficacy. Self-efficacy beliefs affect motivation for change and development. We assume a specific self-efficacy for modifying one's sexual interest in children. Viewing sexual interest in children as immutable may suppress such self-efficacy. Viewing sexual interest in children as changeable may enhance such self-efficacy.